1992
DOI: 10.1111/j.1398-9995.1992.tb02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependency of sensitization to aero‐allergens in asthmatics

Abstract: Skin reactivity (intracutaneous test) to histamine and allergens was studied cross-sectionally in a Dutch asthmatic patient population from childhood to old age (4-75 years). It was found that the histamine skin reactivity rose significantly (p less than 0.05) during childhood, was significantly higher in the 10-15-year age group, and was constant between 20 and 75 years of age. The mean wheal index (histamine ratio) of all allergens was constant during childhood, and decreased after the age of 25 for grass po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
4
33
0
4
Order By: Relevance
“…This is comparable to the rate of 54.3% obtained for the 7- to 12-year-old asthmatics in the present study. In other studies that covered the full age spectrum as the present study, essentially similar results (both in magnitude and age-dependent distribution) were reported [7, 24]. …”
Section: Discussionsupporting
confidence: 75%
“…This is comparable to the rate of 54.3% obtained for the 7- to 12-year-old asthmatics in the present study. In other studies that covered the full age spectrum as the present study, essentially similar results (both in magnitude and age-dependent distribution) were reported [7, 24]. …”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of sensitization to fungi is unclear, although estimates suggest that 3% to 10% of the general population, 12% to 42% of atopic patients, and up to 66% of patients with severe asthma may be sensitized to fungi [9,10,32]; yet, not all sensitized individuals will develop allergic symptoms [5]. Prevalence varies with age [33,34] and can differ between countries [35]. Surveys based on skin prick testing (SPT), which is relatively insensitive for some fungal allergens, may underestimate the prevalence of IgE sensitization.…”
Section: Allergic Immune Responses To Fungimentioning
confidence: 99%
“…Nimeijer et al have demonstrated that the sensitivity of the allergy skin test decreases with age to all allergens except for grass pollen. 26 Consequently, this could lead to a possible desensitisation of a widespread allergens such as pollens in the elderly population. In our study, dysphagia was the most common symptom presentation among elderly EoE patients.…”
mentioning
confidence: 99%